THE NEXUS OF COVID-19 PANDEMIC AND POLICE BRUTALITY PROTESTS IN THE U.S. - Nugraheni Widianingtyas; Achmad Munjid (Universitas Bandar Lampung, 2021)
Dozens of black people die at the hands of law enforcement every year. However, the Black Lives Matter movement and racial justice protests erupted massively in 2020 in response to the death of George Floyd, Breonna Taylor, Rayshard Brooks, Daniel, and many other black victims. It is not just a matter of police shooting. There is another underlying determinant that deserves a deeper investigation contributing to the big chaos last year whose impact is still being felt today. This study intends to discuss the unspoken reasons why Police brutality protests in 2020 were more tense and arousing public concern than in previous years. This study subsumed under a phenomenological study as discriminatory experiences of African-Americans become the main discussion. Further, the analysis of this qualitative study relies on the writer's interpretation. The results show that the vulnerability to the Covid-19 outbreak that began in early 2020 spread unevenly involving race and ethnicity. Black and other minority groups have suffered greater depression as cities with large black populations have become hotspots for the coronavirus and 23% of the deaths from the pandemic are black Americans. The covid-19 outbreak has aggravated the life of black Americans and is a strongly adverse determinant that plays behind the outburst of black Americans' anger at the death of their community members at the hands of police last year.